Pre- and postsynaptic alterations in the visual cortex of the P23H-1 retinal degeneration rat model - Juan R. Martinez-Galan; Maria Garcia-Belando; Jose J. Cabanes-Sanchis; Elena Caminos (Frontiers Media S.A., 2022)
P23H rats express a variant of rhodopsin with a mutation that leads to loss of visual function with similar properties as human autosomal dominant retinitis pigmentosa (RP). The advances made in different therapeutic strategies to recover visual system functionality reveal the need to know whether progressive retina degeneration affects the visual cortex structure. Here we are interested in detecting cortical alterations in young rats with moderate retinal degeneration, and in adulthood when degeneration is severer. For this purpose, we studied the synaptic architecture of the primary visual cortex (V1) by analyzing a series of pre- and postsynaptic elements related to excitatory glutamatergic transmission. Visual cortices from control Sprague Dawley (SD) and P23H rats at postnatal days 30 (P30) and P230 were used to evaluate the distribution of vesicular glutamate transporters VGLUT1 and VGLUT2 by immunofluorescence, and to analyze the expression of postsynaptic density protein-95 (PSD-95) by Western blot. The amount and dendritic spine distribution along the apical shafts of the layer V pyramidal neurons, stained by the Golgi-Cox method, were also studied. We observed that at P30, RP does not significantly affect any of the studied markers and structures, which suggests in young P23H rats that visual cortex connectivity seems preserved. However, in adult rats, although VGLUT1 immunoreactivity and PSD-95 expression were similar between both groups, a narrower and stronger VGLUT2-immunoreactive band in layer IV was observed in the P23H rats. Furthermore, RP significantly decreased the density of dendritic spines and altered their distribution along the apical shafts of pyramidal neurons, which remained in a more immature state compared to the P230 SD rats. Our results indicate that the most notable changes in the visual cortex structure take place after a prolonged retinal degeneration period that affected the presynaptic thalamocortical VGLUT2-immunoreactive terminals and postsynaptic dendritic spines from layer V pyramidal cells. Although plasticity is more limited at these ages, future studies will determine how reversible these changes are and to what extent they can affect the visual system's functionality.